Experiences of Vulnerability in Adult Male Prisoners: An Integrative Review. (January 2023) - Heaslip, Vanessa; Dugdale, Caspian; Parker, Jonathan; Johnsen, Berit; Hean, Sarah
Vulnerability linked to offenders tends to focus on victims and society. Understanding prisoner vulnerability is important to better address the negative impact of prison life. This article reviews the evidence of vulnerability reported by male prisoners. Using the Preferred Reporting Items for Systematic reviews and Meta-Analysis guidelines, 3039 citations were filtered. Data were analyzed using thematic analysis, highlighting four areas of vulnerability: uncertainty, environmental vulnerability, fear of harm, and loss of human connection. The article notes that basic principles for the treatment of prisoners are not met in many areas, indicating a need to shift conceptualizations of vulnerability.